Radiology Education via Social Media—Optimal Utilization of Resources: A Narrative Review - Rai, Santosh; Chugh, Gaurika (Indographics, 2025)
Using social media for radiology education is an innovative and efficient method. By utilizing platforms such as YouTube, X, and Instagram, educators can effectively share information and interact with students. This approach boosts engagement, fosters collaboration, and provides easy access to resources, thereby enhancing the educational experience for both students and teachers. Social media platforms offer a convenient and accessible means for radiology education, enabling the effortless sharing of information and resources. They promote active engagement and discussion among learners, fostering the exchange of ideas and perspectives. Additionally, these platforms support mentorship and networking opportunities within radiology education. And given radiology's rich visual content, it seamlessly integrates into various social media platforms. Knowledgeable use of social media platforms based on its strength of resources available on each platform contributes to efficient online educational content. Social media use in medical education is driven by the change in the learner as a connected, creative, and collective subject. Although there are many advantages, however, educators face challenges such as ensuring accuracy, maintaining privacy, and combating misinformation. When used effectively, social media significantly enhances radiology education by promoting learning, collaboration, and professional development. With recent advances like augmented reality, virtual reality, and gamification coming into field of education, it is further going to revolutionize the educational power of social media.
Keywords: radiology resources; social media radiology; online education; educational resources; radiology education; e-learning; virtual radiology